2011
DOI: 10.1109/tit.2011.2162276
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Silver Codes

Abstract: For an n t transmit, n r receive antenna system (n t × n r system), a full-rate space time block code (STBC) transmits n min = min(n t , n r ) complex symbols per channel use. The well known Golden code is an example of a full-rate, full-diversity STBC for 2 transmit antennas. Its ML-decoding complexity is of the order of M 2.5 for square M -QAM. The Silver code for 2 transmit antennas has all the desirable properties of the Golden code except its coding gain, but offers lower ML-decoding complexity of the ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
(100 reference statements)
0
16
0
Order By: Relevance
“…In Appendix B, it is shown that O l = O ′ l almost surely as SN R → ∞. As a result, in the high SNR scenario, (20) becomes…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…In Appendix B, it is shown that O l = O ′ l almost surely as SN R → ∞. As a result, in the high SNR scenario, (20) becomes…”
Section: Resultsmentioning
confidence: 94%
“…There exist several low-ML-decoding complexity LSTBC-schemes that have a code-rate less than n t complex dimensions per channel use and are equipped with the NVD property. Examples of these for asymmetric MIMO systems are rate-n r LSTBCschemes that are based on fast-decodable LSTBCs [15] from cyclic division algebras, LSTBC-schemes from co-ordinate interleaved orthogonal designs [16], and four-group decodable LSTBC-schemes [17]- [20]. For these LSTBC-schemes, the sufficient criterion provided in [4] for DMT-optimality, which requires that LSTBCs have a code-rate of n t complex dimensions per channel use irrespective of the number of receive antennas, is not applicable.…”
Section: A Motivation For Our Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The so-called fast decodable STBCs [2], [3], [5]- [7] exploit the orthogonality embedded in the codewords and achieve ML decoding performance at a low decoding complexity. For instance, Biglieri-Hong-Viterbo (BHV) constructed a rate-2 STBC [2] based on the classical Jafarkhani code [1].…”
Section: Introductionmentioning
confidence: 99%
“…This construction idea was then generalized to rate-2 STBC case [5]. Srinath and Rajan (Srinath-Rajan) proposed a fastdecodable rate-2 STBC [6], [7] based on co-ordinate interleaved orthogonal design (CIOD) [8]. The Srinath-Rajan code possesses high coding gain but needs low decoding complexity due to its orthogonal structure.…”
Section: Introductionmentioning
confidence: 99%